Sejarah Peradaban Islam Masa Kepemimpinan Khalifah Usman bin Affan Radhiallahu Anhu - Hidayat, Tatang; Istianah, Istianah; Aprilianti, Tia; Syafe'i, Makhmud; Anwar, Saepul (PT. Student Rihlah Indonesia, 2025)
The purpose of this research is to analyze the history of Islamic civilization during the leadership of Caliph Usman bin Affan. This research uses a qualitative approach and literature study method. Based on the results of the research, the expansion of Islam during 'Uthmān's time can be summarized in two areas, namely suppressing the disobedience and rebellion that occurred in several countries that had come under Islamic rule at the time of Umar and continuing the expansion of Islam to areas that had stopped the expansion of Islam during the time of Umar. 'Uthmān handed over the whole of the Levant to Muawiyyah ibn Abu Sufyan to wage war by sea and land as far as Taflis. Then 'Abdullah ibn Abu Sarh conquered all of Africa. At that time, 'Uthmān released 'Amr b. 'Ash from his position as the governor of Egypt and appointed 'Abdullah b. Abu Sarh in his place. 'Uthmān b. Affan r.a was besieged by rebels. It happened in the month of Dhul Hijjah in the 35th year of Hijrah. At that time he was 82 years old and his caliphate lasted 12 years. His killing was the cause of the division and scattering of the Muslims.